New discoveries from MESSENGER and insights into Mercury's exosphere. Issue 22 (19th November 2016) - Vervack, R. J.; Killen, R. M.; McClintock, W. E.; Merkel, A. W.; Burger, M. H.; Cassidy, T. A.; Sarantos, M.
Abstract: For most of the orbital phase of the MErcury Surface, Space ENvironment, GEochemistry, and Ranging (MESSENGER) mission, a regular search for weakly emitting or less abundant species in Mercury's exosphere resulted in nondetections. However, during the final Earth year of the mission, emission from multiple lines of manganese, aluminum, and ionized calcium was detected. These observations validate the detection of a single line of ionized calcium during the third MESSENGER Mercury flyby, provide definitive confirmation for weak aluminum detections in ground‐based observations, and represent the discovery of manganese in Mercury's exosphere. These detections occurred over a limited range of predawn local times and Mercury true anomaly angles (0°–70°), and each has a distinct spatial distribution. Equally interesting is the absence of detectable emission from oxygen at limits well below the levels reported for Mariner 10. Key Points: Discovery of manganese emission in Mercury's exosphere and unambiguous confirmation of emission from aluminum and ionized calcium Emissions occurred at predawn local times between 0° and 70° Mercury true anomaly angle and exhibit different spatial distributions Oxygen emission was not detected at limits well below the values reported from Mariner 10